Characteristics of an Altered Diabase Dike in a Coal Seam: A Case Study from the Datong Coalfield, Shanxi, China. (7th July 2020) - Song, Xiaoxia; Li, Kaijie; Ma, Hongtao; Liu, Dongna; Zhao, Jingui; Zhou, Jiarui
Abstract : Carboniferous–Permian coal seams in the Datong coalfield are intruded by Mesozoic magmatic dikes and sills. Our observations indicate that these dikes and sills have been seriously altered and have lost their original characteristics. Although this phenomenon has been mentioned in some studies, there is a lack of detailed research on the alteration mechanism. To fill this research gap, six dike samples were collected in this study to analyze their alteration characteristics and mechanisms. Petrographic analysis, scanning electron microscopy, and X-ray diffraction were used to determine the mineralogy of the altered igneous samples. The results suggest that the mineral alteration is associated with severe carbonation and clavization. The carbonation of mafic minerals is due to the release of CO2 generated from the coking of high volatile bituminous coals that may have occurred during the intrusive event. However, labradorite did not react with CO2 . The water activity in the coal seam was enhanced by the dikes, and mafic minerals were converted into mixtures of chlorite and smectite group minerals. The water activity is especially high at the edges of the dike. Albite and clay minerals were formed due to the albitization of labradorite. Based on these effects, the dike can be divided into weak alteration, carbonation, and clavization bands. The alteration processes in the coal seam are described in detail in this work, and potential formation mechanisms are suggested.